Effectiveness of Village Asset Management in Ciakar Village, Cipaku District, Ciamis Regency - Rizal Ibrahim; Arie Budiawan; Erlan Suwarlan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
his study examines the effectiveness of village asset management in Ciakar Village, Cipaku District, Ciamis Regency. This village has strategic assets of great value, such as the Ciakar Multipurpose Reservoir established in 2019 using the state budget of Rp. 12,500,000,000, and Murbey Nature Tourism with an asset area of 176,400 m2, but the two land assets have not provided economic benefits for the community and Village Original Income (PADes). The purpose of this study is to find out and analyze in more depth about: The Effectiveness of Village Asset Management based on the concept of asset management according to Siregar, (2004), namely: asset inventory, legal audit, asset valuation, asset optimization, asset supervision and control. This study uses a descriptive qualitative method with a case study approach. Data were collected through interviews through purposive sampling and snowball sampling techniques, observation, and documentation. The data analysis technique refers to the Miles and Huberman model which consists of data reduction, data presentation, and conclusion drawn. The results of the study show that the effectiveness of village asset management in Ciakar Village, Cipaku District, Ciamis Regency has not been effective in the five dimensions studied. Asset inventory is still carried out unsystematically with data that is not up-to-date, legal audits have not been carried out seriously, it is proven that there is no legal basis for some assets, asset valuations have not been carried out regularly and standardized so that the economic value of assets is not measurable, asset optimization has not been achieved due to the lack of institutional cooperation and potential-based planning on assets, and asset supervision and control are still administrative without physical evaluation. routine and adequate community participation. The researcher recommends a comprehensive overhaul of the asset management system, including updating inventory data, completing asset legality, periodic asset assessments, preparing strategic plans, and strengthening a transparent and participatory supervisory system.Keywords: Effectiveness, Village Asset Management, Asset Management, Ciakar Village